Modern information technologies as a tool for reducing working population poverty - A. G. Karimov; G. R. Fatkullina (Цифровая социология)
Rapid development and implementation of modern information and communication technologies has led to a new phase of economic, scientiﬁc and technological progress. However, there is no mechanism to ensure social systems effective management based on the information technologies use due to socio-economic inequality among the population of the Russian Federation, preventing all segments of the population from beneﬁting scientiﬁc and technological progress results, which has been exacerbated by the COVID-19 pandemic. The aim of the study is to identify the modern information technologies role in improving the living standard and the population life quality, in particular, in overcoming the working population poverty. The article analyses foreign and domestic research on this issue over the past ﬁve years. The pandemic impact on social structures, in particular the labour market and employment, has been considered. The growing importance and social networks role in public life and their use serious potential to solve the problems under study have been noted. The authors carried out a sociological survey in the Republic of Bashkortostan, on the basis of which made conclusions: modern society is characterised by the information inequality problem, which is closely linked to the economic inequality problem, which will be exacerbated by the modern information and communication technologies development; the computer illiteracy problem and the close relationship between income level and knowledge, skills in information and communication technologies, English language skills were identiﬁed among residents. The research results highlight the need to implement modern information technologies skills into poverty alleviation programmes.